Unequal electoral participation: the negative effects of long work hours and unsociable work schedules in Europe - Jianghong Li; Heiko Giebler; Rebecca Wetter; Hannah Kenyon Lair; Julia Ellingwood (European Journal of Politics and Gender, 2023)
Considering gender inequality in time as a resource for political participation and using Wave 5 of the European Social Survey data on 24 European countries, this study examines: (1) the relationship of both long working hours and unsociable work schedules to participation in national elections in Europe before or during 2010; (2) factors that may mediate this association; and (3) gender differences in this relationship and occupation-specific patterns. The findings show that both working more than 45 hours per week and working evenings, nights or weekends are associated with lower national electoral participation in women with both high and low occupational status. Among men with the lowest occupational status, working long hours is also linked to lower participation. These findings are robust against controlling for important confounders. Political interest seems to partially mediate the negative effect of unsociable work schedules on voting in women. Neither health nor social engagement plays a mediation role.
Keywords: 320; long work hours; unsociable work schedules; electoral participation; gender; occupational status; Europe